Marshall Fire's impact on Colorado housing market - Sharma, Rukuma, author; Arneson, Erin, advisor; Valdes-Vasquez, Rodolfo, advisor; Bhattarai, Niroj, committee member (Colorado State University. Libraries, 2024)
The devastation caused by wildfires not only results in the loss of human lives and property but also significantly impacts the residential housing real estate market in the United States. With the rise in urban and suburban wildfires and brushfires, as well as increased human settlement across the Wildlife Urban Interface (WUI) zone, it is imperative to analyze how wildfires in less rural areas impact the housing market. While previous studies have explored the impact of disasters on the housing market, only a few studies have focused specifically on how wildfires affect the residential housing market in the United States. Out of those, there are only limited studies about wildfires in suburban and urban communities. This research focuses on examining the aftermath of the Marshall Fire, a brushfire that occurred in a suburban region near Boulder, Colorado, in December 2021, causing damage to over 1,000 residential homes. The study investigates the impact of the Marshall Fire on the residential housing market in Colorado, aiming to achieve two primary objectives: 1) determine the extent and timing of changes in housing values following the Marshall Fire, and 2) assess how geographical proximity to the fire zone affected housing values. The study collects secondary data on the monthly housing values for Marshall Fire-affected zip codes and surrounding areas in Colorado from Zillow. Data from before and after the wildfire was analyzed to identify the extent of the impact of the Marshall Fire on home values. Results indicate a significant increase in median housing values in the fire-affected region. Housing values spiked two months post-fire, remained inflated for six months post-fire, and gradually returned to pre-fire trends after six months. Before the Marshall Fire, housing values in fire-affected zip codes consistently lagged behind surrounding and other Colorado zip codes for 14 months. Statistical tests, including paired t-tests and repeated measures ANOVA tests, indicate that the changes in housing values pre-fire and post-fire are statistically significant. The geographic proximity of a home to the Marshall Fire also played a statistically significant role in housing value changes. This surge in housing values could be attributed to supply and demand dynamics in the real estate market. The research contributes valuable insights into the effects of suburban fires on the residential housing market, aiding stakeholders in making informed decisions for the future. The study's findings offer valuable guidance for homebuyers, sellers, and the general public in predicting housing market trends in the event of similar incidents, facilitating informed decision-making.